2010
DOI: 10.1111/j.1601-183x.2010.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic variants of the metabotropic glutamate receptor 3 (GRM3) and cognitive set shifting in healthy individuals

Abstract: Set-shifting and maintenance are complex cognitive processes, which are often impaired in schizophrenia. The genetic basis of these processes is poorly understood. We aimed to investigate the association between genetic variants of the metabotropic glutamate receptor 3 (GRM3) and cognitive set-shifting in healthy individuals. The relationship between 14 selected single nucleotide polymorphisms (SNPs) of the GRM3 gene and cognitive set-shifting as measured by perseverative errors using the modified card sorting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
(44 reference statements)
2
9
0
Order By: Relevance
“…Second, variants in GRM3 were associated with the maintenance of pursuit which requires active dynamic interaction across corticocortical circuitry for perceptual analysis and action planning. GRM3 codes for the type 3 metabotropic glutamate receptor (mGluR3) protein that is essential for optimal glutamate signaling in the brain, notably in prefrontal cortex as has been shown previously with other neurocognitive processes in psychotic disorders [44,45,47]. Together, these preliminary findings demonstrate linkage of specific neurophysiological parameters with particular functional polymorphisms that regulate brain neurochemistry in ways believed to be fundamental in the pathophysiology of psychotic disorders.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Second, variants in GRM3 were associated with the maintenance of pursuit which requires active dynamic interaction across corticocortical circuitry for perceptual analysis and action planning. GRM3 codes for the type 3 metabotropic glutamate receptor (mGluR3) protein that is essential for optimal glutamate signaling in the brain, notably in prefrontal cortex as has been shown previously with other neurocognitive processes in psychotic disorders [44,45,47]. Together, these preliminary findings demonstrate linkage of specific neurophysiological parameters with particular functional polymorphisms that regulate brain neurochemistry in ways believed to be fundamental in the pathophysiology of psychotic disorders.…”
Section: Discussionsupporting
confidence: 61%
“…Alterations of D2 receptor functions have been related to psychotic symptoms making the D2 receptor a primary target of dopamine antagonists including antipsychotic agents [42,43]. GRM3 polymorphisms are believed to contribute to susceptibility to psychosis, altered cognitive function, altered prefrontal cortical levels of N-acetylaspartate/creatine [44-47] and the regulation of synaptic glutamate concentrations via effects on astrocytes [48]. Both genes have not previously been studied in relation to pursuit deficits in psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…For rs6465084, a previous study has shown a dominant effect of the G allele (AA and G carriers) (Mossner et al, 2008). The other two SNPs (rs2299225 [TT and G carriers] and rs1468412 [AA and T carriers]) were divided into two groups because the numbers of minor alleles were too small, in line with a previous study (Baune et al, 2010). Finally, we ran a correlation analysis using Spearman's rank correlation coefficients between [oxy-Hb] changes and demographic characteristics.…”
Section: Discussionmentioning
confidence: 93%
“…In line with the previous studies, since the small number of samples of the minor allele in each SNP did not permit further analysis, we combined two genotype subgroups into one "carrier" group for the three SNPs: rs274622, rs2299225, and rs1468412 (Baune et al, 2010). We did not conduct between-genotype comparison for rs6465084 SNP because the representation of the G carriers in the patients with schizophrenia was too small (n = 4).…”
Section: Basic Characteristics Of Study Participantsmentioning
confidence: 89%
“…Additionally, there have been implications that the GRM3 gene is involved with various domains of cognitive function (Roffman et al, 2006), but any associations between rs12704290 and cognitive dysfunction have yet to be evaluated. A previous study stated that perseverative error processing appears to be not only a marker of frontal lobe dysfunction in SCZ but also a vulnerability marker of SCZ (Baune et al, 2010). To better understand the interaction between the GRM3 gene and perseverative error processing in pathological conditions, our secondary purpose was to evaluate the relationship between GRM3 polymorphisms and perseverative error processing in SCZ patients.…”
Section: Introductionmentioning
confidence: 99%